Assessment Awareness about Hand Hygiene among Health Care Providers in Hospitals at Al_Nasiriyah City: Penilaian Kesadaran tentang Kebersihan Tangan di antara Penyedia Layanan Kesehatan di Rumah Sakit di Kota Al_Nasiriyah - Teeba T. Khudair (Academia Open, 2024)
Background: The World Health Organization emphasizes hand hygiene as a crucial method for controlling hospital infections, emphasizing the need for healthcare workers to have current knowledge on this topic.. Objective: The study evaluates hand hygiene awareness among healthcare providers in AL_Nasiriyah hospitals, identifying factors influencing HH abidance, crucial for patient safety and reducing infectious disease transmission. Methods: A cross-sectional study was conducted in various hospitals in the governorate of AL_Nasiriyah city during the period from May to July 2024 to evaluate awareness Associated to (HH) hygiene among health care providers.by using a special format which included two parts, the first part related to their demographic characteristic and the second part contain multiple questions A purposive sample is selected for the study which sample consisting (171) working various specializations .Date were gathered through the interviewed in workplace and analyzed by using spss 20 through the application of descriptive statistical included (frequencies, percentages, M.S,and S.D). The overall result: The study revealed that over thirty-two percent of the population (63.2%) and those with over six years of health experience have the highest awareness of hand hygiene, influenced by education and experience. Conclusion: This study shows a good level of awareness of hand hygiene among health care practitioners at mean score (1.39) level of awareness regarding answering the questionnaire information. Recommendations: The study suggests continuous training for competent authorities, provision of basic hand hygiene environments, alcohol and sterilizers, and recent hygiene items for health places.